(untitled) (Journal of Faculty of Education, 2021)
This study aimed at identifying the impact of using power point program in teaching mathematics to the second level students of secondary school in the locality of Karari. The researcher followed descriptive and experimental approach. The population from which the study sample is drawn consisted of 2406 students. The samples were randomly selected from the study population. The samples consisted of 24 students from Al Soraa bint Khabeer Secondary School for girls. The researcher used a achievement test as a tool to collect data from the study samples, along with the computerized educational program. By following the appropriate statistical methods, the data were analyzed using the statistical package for the social science (SPSS). The most important results of this study are: The use of power point slides has a great positive impact on student’s understanding and significant statistical differences in the average understanding of the students selected for the study. The study finishing the following recommendations: it’s of great importance to provide schools in public education sector with computers, encourage teachers to learn using computers in teaching mathematics’ and keep the pace with every new trend in this field.